How to Investigate Within-Subject Associations between Physical Activity and Momentary Affective States in Everyday Life: A Position Statement Based on a Literature Overview - Kanning, Martina K.; Ebner-Priemer, Ulrich W.; Schlicht, Wolfgang M. (Frontiers in Psychology, 2013)
Several meta-analyses have investigated the association between physical activity and affective states and have found evidence suggesting that exercise exerts a positive effect on affective state. However, in this field of research, most studies have conducted between-subject analyses. Nonetheless, there is more and more interest in the within-subject associations between physical activity and momentary affective states in everyday life. This position statement pertains to this up-and-coming field of research and provides methodological recommendations for further studies. The paper is divided into three parts: First, we summarise and evaluate three methodological requirements necessary for the proper evaluation of within-subject associations between physical activity and momentary affective states in everyday life. We propose that the following issues should be considered: a) to address the dynamic nature of such relationships, repeated assessments are necessary; b) as activities performed in everyday life are mostly spontaneous and unconscious, an objective assessment of physical activity is useful; c) given that recall of affective states is often affected by systematic distortions, real-time assessment is preferable. In sum, we suggest the use of ambulatory assessment techniques, and more specifically the combination of acceloremeter-assessment of physical activity with an electronic diary assessment of the momentary affective state and additional context information. Second, we summarise 22 empirical studies published between 1980 and 2012 using ambulatory assessment to investigate within-subject associations between momentary affective states and physical activity in everyday life. Generally, the literature overview detects a positive association, which appears stronger among those studies that were of high methodological quality. Third, we propose the use of ambulatory assessment intervention strategies to change people's behaviour (ambulatory assessment int